Design and synthesis of natural antibacterial derivatives for ocular tuberculosis: a comprehensive review - Osei Duah, Isaiah; Amankwah, Gabriel; Ampong, Josephine; Brown, Sherlene; Tettey, Bernice Lebene; Acheampong, Hubert Osei; Awuku, Ruth Boahemaa; Danquah, Cynthia Amaning (Frontiers in Pharmacology, 2025)
Ocular tuberculosis (TB) is an underrecognized extrapulmonary manifestation of Mycobacterium tuberculosis (M. tuberculosis) infection that can result in irreversible vision loss. Current systemic therapies, including isoniazid, rifampicin, pyrazinamide, and ethambutol, are often inadequate in achieving therapeutic intraocular concentrations and may pose ocular toxicity risks. The eye’s unique anatomical and physiological barriers, including the cornea, blood–aqueous, and blood–retinal barriers, limit drug penetration, particularly to the posterior segment. This paper explores the potential of natural antibacterial compounds as candidates for ocular TB therapy, emphasizing on rational drug design, chemical modification, and targeted drug delivery. Phytochemicals such as, plant-derived alkaloids, flavonoids, terpenoids, quinone, polyphenols, and saponins offer promising antibacterial scaffolds, which can be optimized for ocular bioavailability and safety through structural modification, prodrug strategies, and hybridization with other bioactive moieties. Advanced drug delivery systems, including nanoparticles, liposomes, nanogels, sustained-release implants, and in situ gelling systems, can overcome ocular barriers and maintain therapeutic drug concentrations. Preclinical evaluation using in vitro, ex vivo, and in vivo ocular models is critical to assess antimicrobial efficacy, pharmacokinetics, and toxicity. Clinical translation requires careful integration with systemic therapy, robust trial design, and navigation of regulatory frameworks, with particular attention to resource-limited settings. Future directions include computational modeling, personalized therapy, and global accessibility to ensure equitable implementation. By combining natural product chemistry, innovative drug delivery strategies, and translational research, next-generation ocular TB therapies have the potential to prevent vision loss and improve patient outcomes worldwide.